Use of Virtual Reality Tools for Vestibular Disorders Rehabilitation: A Comprehensive Analysis. (30th April 2015) - Bergeron, Mathieu; Lortie, Catherine L.; Guitton, Matthieu J.
Abstract : Classical peripheral vestibular disorders rehabilitation is a long and costly process. While virtual reality settings have been repeatedly suggested to represent possible tools to help the rehabilitation process, no systematic study had been conducted so far. We systematically reviewed the current literature to analyze the published protocols documenting the use of virtual reality settings for peripheral vestibular disorders rehabilitation. There is an important diversity of settings and protocols involving virtual reality settings for the treatment of this pathology. Evaluation of the symptoms is often not standardized. However, our results unveil a clear effect of virtual reality settings-based rehabilitation of the patients' symptoms, assessed by objectives tools such as the DHI (mean decrease of 27 points), changing symptoms handicap perception from moderate to mild impact on life. Furthermore, we detected a relationship between the duration of the exposure to virtual reality environments and the magnitude of the therapeutic effects, suggesting that virtual reality treatments should last at least 150 minutes of cumulated exposure to ensure positive outcomes. Virtual reality offers a pleasant and safe environment for the patient. Future studies should standardize evaluation tools, document putative side effects further, compare virtual reality to conventional physical therapy, and evaluate economical costs/benefits of such strategies.